Effect of total dissolved solids and pH on the growth and yield of spinach (Spinacia oleracea L.) in the aeroponic system - Le Huu , Dat; Nguyen Trinh Nhat , Hang; Ngo, Xuan Quang (Academia Journal of Biology, 2024)
A study on the total dissolved solids and pH on the growth and yield of spinach (Spinacia oleracea L.) in an aeroponic system was carried out at the Tien Giang Center of Applied Research and Science Technology Services in 2024. The study aimed to determine the effectiveness level of total dissolved solids and pH on the promotion of plant growth and yield of spinach in an aeroponic system. The two-factor experiment was arranged in a completely randomized design with nine treatments and five repetitions. Total dissolved solids have 3 levels: 1,000 ppm; 1,200 ppm and 1,400 ppm corresponding to A1, A2 and A3. pH has 3 levels: 6.0, 6.5 and 7.0 corresponding to B1, B2 and B3. Nine treatments to incorporate total dissolved solids and pH include: A1B1 (1,000 ppm/6.0), A1B2 (1,000 ppm/6.5), A1B3 (1,000 ppm/7.0), A2B1 (1,200 ppm/6.0), A2B2 (1,200 ppm/6.5), A2B3 (1,200 ppm/7.0), A3B1 (1,400 ppm/6.0), A3B2 (1,400 ppm/6.5) and A3B3 (1,400 ppm/7.0). Results showed that spinach grew well in the aeroponic systems with total dissolved solids at 1,200–1,400 ppm and pH at 6.0–6.5. Our results show that, from 10 days to 20 days after transplanting, there is an interaction between the factors “total dissolved solids” and “pH”, affecting the growth and development of spinach in the aeroponics system, with differences between pairs of treatments. However, statistical analysis did not find the interaction between factors “total dissolved solids” and “pH” affecting the yield of spinach in aeroponic systems. In the treatments, A3B1 (1,400 ppm/6.0) results in terms of number of leaves (27.50 ± 0.14 leaves/plant), Plant height (44.82 ± 1.16 cm), leaf length (28.86 ± 1.62 cm), leaf width (14.40 ± 1.37 cm), root length (87.42 ± 4.33 cm) were higher than in other treatments.